2010
DOI: 10.1155/2010/910686
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacological and Toxicological Profile of Silver as an Antimicrobial Agent in Medical Devices

Abstract: Silver is used widely in wound dressings and medical devices as a broad-spectrum antibiotic. Metallic silver and most inorganic silver compounds ionise in moisture, body fluids, and secretions to release biologically active Ag+. The ion is absorbed into the systemic circulation from the diet and drinking water, by inhalation and through intraparenteral administration. Percutaneous absorption of Ag+ through intact or damaged skin is low. Ag+ binds strongly to metallothionein, albumins, and macroglobulins and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
231
1
19

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(256 citation statements)
references
References 131 publications
5
231
1
19
Order By: Relevance
“…The slow and steady reactions of silver sulfadiazine with sodium-chloride containing body fluids such as serum and exudate permit slow and sustained delivery of silver ions into the wound area [12,13].…”
Section: Mechanism Of Action Of Silver and Silver Sulfadiazinementioning
confidence: 99%
See 1 more Smart Citation
“…The slow and steady reactions of silver sulfadiazine with sodium-chloride containing body fluids such as serum and exudate permit slow and sustained delivery of silver ions into the wound area [12,13].…”
Section: Mechanism Of Action Of Silver and Silver Sulfadiazinementioning
confidence: 99%
“…Silver ions are active against a broad range of microorganisms: bacteria, fungi and viruses, including many antibiotic-resistant bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA) and Vancomycin-resistant Enterococci (VRE) [13].…”
Section: Mechanism Of Action Of Silver and Silver Sulfadiazinementioning
confidence: 99%
“…Silver has long been used as an antimicrobial agent in medicine to keep wounds clean since the days of ancient Greece, Egypt, and Rome (Chen & Schluesener, 2008;Lansdown, 2010). This is because of the efficacy of thiol group reactions which inactivate bacterial enzymatic activity (Faunce & Watal, 2010).…”
Section: A Clinical Medicine Perspective Of Silver and Nanosilvermentioning
confidence: 99%
“…Lorenzetti et al 11 used hydrothermal treatments to generate nanorough surfaces on titanium and found that macro-and microscale grooves (results of the initial material machining process) provided niches for bacteria to adhere and proliferate on, despite high roughness values. Silver is one of the most prominent non-small-molecule drugs used for antibacterial applications, 3,[17][18][19] but can be expensive and mildly toxic to surrounding mammalian cells. 20,21 Additionally, adding different materials to the surface may lead to imperfectly fused layers that may eventually wear or delaminate from the bulk implant.…”
Section: Introductionmentioning
confidence: 99%